Enantiomeric separation of triacylglycerols containing fatty acids with a ring (cyclofatty acids) - Palyzová, Andrea; Řezanka, Tomáš (Journal of chromatography. A, 2020)
Triacylglycerols (TAGs) containing cyclofatty acids (cycloFAs) from two oilseeds of Sterculia foetida and Hydnocarpus wightiana were analysed using both reversed-phase (RP18) and chiral phase columns. TAGs were identified using high-resolution electrospray ionization mass spectrometry in the positive ion mode. Fifty-five molecular species of TAGs have been identified in sterculic oil, 27 of which contained at least one cyclopropenyl-FA (e.g., malvalic or sterculic acids). The structures of regioisomers and enantiomers were determined for five major TAGs with cyclopropenyl-FAs. One hundred thirty-six TAGs were identified in chaulmoogra oil, 71 of which contained at least one cyclopentenyl-FA (e.g., gorlic, chaulmoogric, and hydnocarpic acids, etc.). Furthermore, in three molecular species, regioisomers and enantiomers were identified using HPLC on a chiral phase column. Eight molecular species of TAGs were prepared through organic synthesis to facilitate the identification of enantiomers. Retention times of fatty acid-containing triacylglycerols with one ring and one double bond are very similar to triacylglycerols with a dienoic fatty acid, but elution times are shorter. For example, dimalvaloylpalmitate elutes earlier than dilinoleylpalmitate. The order of elution of TAGs on the chiral column differs. In TAGs with 2 degrees of unsaturation (ring and double bond, e.g. PStP-StPP-PPSt), the order of elution is symmetric-asymmetric-asymmetric TAGs. TAGs with 4 degrees of unsaturation (one ring and three double bonds or two rings and two double bonds) present a different pattern. When TAGs contain two rings and two double bonds, the order of elution TAGs is asymmetric-symmetric-asymmetric (StStP-StPSt-PStSt); when TAGs contain a ring and 3 double bonds, the elution order is symmetric-asymmetric-asymmetric TAGs (OStO-StOO-OOSt). In species with a higher degree of unsaturation (e.g., 5), the elution order of the TAGs is asymmetric-asymmetric-symmetric (e.g. CCO-OCC-COC).
Keywords: Sterculic seeds; mastné kyseliny; Non-aqueous reversed-phase-HPLC; Cyclic fatty acids; Fatty Acids, Monounsaturated; Chromatography, Reverse-Phase; Fatty Acids; Sterculia; triglyceridy; vysokoúčinná kapalinová chromatografie; Triglycerides; Plant Oils; chromatografie s reverzní fází; Stereoisomerism; stereoizomerie; cyklopropany; Triacylglycerols; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, High Pressure Liquid; oleje rostlin; Chaulmoogra oil; Enantiomeric separation; kyseliny mastné mononenasycené; Cyclopropanes; Spectrometry, Mass, Electrospray Ionization